2001
DOI: 10.1046/j.0956-540x.2001.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas hydrate stability and the assessment of heat flow through continental margins

Abstract: Summary A prominent feature across some continental margins is a bottom‐simulating reflector (BSR). This seismic reflection generally coincides with the depth predicted for the base of the gas hydrate stability field. Because the occurrence of gas hydrates is controlled by temperature and pressure conditions, it has been suggested that BSRs mark an isotherm and they have therefore been used to estimate the heat flow through continental margins; crucial parameters are the temperature at BSR depth and at the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
144
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 56 publications
(196 reference statements)
3
144
0
Order By: Relevance
“…The program is available online at http://hydrates.mines.edu/CHR/Software.html. Additionally, sites reported in Table 1 with known pressure and temperature conditions from drilling at the base of gas hydrate stability and those reported by Grevemeyer and Villinger [2001] are included (Sites 889,892,(859)(860)(861)688,and 808). Error bars reflect uncertainties in the depth of the base of gas hydrate stability zone and geothermal gradients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The program is available online at http://hydrates.mines.edu/CHR/Software.html. Additionally, sites reported in Table 1 with known pressure and temperature conditions from drilling at the base of gas hydrate stability and those reported by Grevemeyer and Villinger [2001] are included (Sites 889,892,(859)(860)(861)688,and 808). Error bars reflect uncertainties in the depth of the base of gas hydrate stability zone and geothermal gradients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Two scenarios of the gas hydrate phase boundary are included for seawater (35 ppt) and methane gas, and an arbitrary mix of 90% methane and 10% ethane (with seawater of 35 ppt). We also added previously published data [Grevemeyer and Villinger, 2001] to complete the data set, although some of these sites did not yield useable information for depth to the TGHOZ or the depth to the BGHSZ. Most plotted sites fall between the pure water and seawater gas (methane) hydrate stability boundaries.…”
Section: 1002/2017gc006805mentioning
confidence: 99%
“…Hyndman et al [15] concluded that in situ data favour a base of the hydrate stability field controlled by the pure methane/pure water phase boundary. However, other authors (e.g., [12,16]) have favoured the pure methane/seawater boundary, and this boundary better fits the data from recent Ocean Drilling Program (ODP) legs [12] (Fig. 4).…”
Section: Heat Flowmentioning
confidence: 72%
“…No in situ data are available for our survey area, and borehole data show a scatter of +/À 20% or more in thermal conductivity for unconsolidated sediments at a given depth in the upper 500 m of the sediment column in similar accretionary wedge settings [12,17]. We could have used a depth-dependent value that accounted for compaction by relating the conductivity to seismic velocity (following [18]), but have instead used a constant value as suggested by [12], since the predicted variation with depth is small.…”
Section: Heat Flowmentioning
confidence: 99%
See 1 more Smart Citation